Intelligible Beauty. (31st May 2022) - Shelley, James
Abstract: Arthur Danto argued from the premiss that artworks are essentially cognitive to the conclusion that they are incidentally aesthetic. I wonder why Danto, and the very many of us he persuaded, came to believe that the cognitive and the aesthetic oppose one another. I argue, contrary to Danto's historical claims, that the cognitive and the aesthetic did not come into opposition until the late nineteenth or early twentieth century, and that they were brought into opposition for reasons of art-critical expediency rather than philosophical necessity. I conclude that a robustly cognitive notion of the aesthetic remains an option for us.